Redescription of the cheloniellid euarthropod Triopus draboviensis from the Upper Ordovician of Bohemia, with comments on the affinities of Parioscorpio venator. (13th September 2022) - Van Roy, Peter; Rak, Štěpán; Budil, Petr; Fatka, Oldřich
Abstract: Cheloniellida is a rare but significant clade of artiopod euarthropods, and a major component of Vicissicaudata alongside aglaspidids. The first cheloniellid to be described was Triopus draboviensis, based on a single specimen from the Upper Ordovician Letná Formation in Bohemia. Because this specimen was believed to be missing its anterior, Triopus draboviensis has been the subject of considerable speculation regarding its affinities, with several authors combining various isolated cephalic shields with its trunk. Notwithstanding, Triopus draboviensis has eluded detailed restudy in the 150 years since its first description. Here we provide a redescription of the holotype and hitherto only known specimen of Triopus draboviensis, and describe a recently discovered second partial specimen as Triopus sp. It is shown that the holotype of Triopus draboviensis preserves the complete cephalic shield, while the trunk reveals a likely articulating device, which may represent an apomorphy for Cheloniellida. Further information on the trunk morphology provided by the new specimen has allowed a complete reconstruction of the dorsal exoskeleton of Triopus . An assessment is made of fossils previously suggested to represent the cephalic shield of Triopus draboviensis ; while it is shown that none of those fossils can be attributed to Triopus, it is reaffirmed that Drabovaspis complexa likely does belong to Cheloniellida, making Drabovaspis the third cheloniellid genus known from the Letná Formation, after Triopus and Duslia . A revised diagnosis for Cheloniellida is provided, and the recently described problematic euarthropod Parioscorpio venator from the Silurian of Wisconsin is firmly rejected from this clade.